UNIFORM CIVIL CODE IN INDIA: CONSTITUTIONAL VISION, CHALLENGES, AND PROSPECTS - Dr. Thanabhai Varjangabhai Rajput (International Educational Journal of Science and Engineering, 2026)
The Uniform Civil Code (UCC) has remained one of the most debated subjects in Indian constitutional and legal discourse since the adoption of the Constitution. Enshrined under Article 44 of the Directive Principles of State Policy, the UCC aims to establish a common set of civil laws governing matters such as marriage, divorce, inheritance, adoption, and succession for all citizens, irrespective of their religion. The concept reflects the constitutional vision of promoting national integration, equality, and social justice while ensuring uniformity in the application of personal laws. Despite its constitutional significance, the implementation of a Uniform Civil Code continues to face numerous legal, social, political, and cultural challenges. India is characterized by remarkable religious and cultural diversity, with different communities following distinct personal laws rooted in their customs and traditions. Consequently, concerns have been raised regarding the potential impact of a uniform legal framework on religious freedom and minority rights protected under the Constitution. The debate surrounding the UCC often involves balancing the principles of equality and secularism with the preservation of cultural pluralism. This research paper examines the constitutional foundations of the Uniform Civil Code and analyzes its relevance in the contemporary Indian legal system. It explores the judicial approach adopted by Indian courts, particularly the observations of the Supreme Court in various landmark cases advocating legal reform and gender justice. The study further evaluates the practical obstacles to implementation, including political resistance, social sensitivities, and the complexities arising from diverse personal law systems.